Using the IBM Spectrum Accelerate family in VMware environments : IBM XIV, IBM FlashSystem A9000 and IBM FlashSystem A9000R, and IBM Spectrum Accelerate - Oscheka, Markus (IBM redpaper., 2018)
This IBM® Redpaper™ publication is a brief overview of synergistic aspects between various VMware offerings and the IBM Spectrum™ Accelerate family, including IBM XIV® and IBM FlashSystem® A9000 and IBM FlashSystem A9000R servers. After reviewing different integration concepts and explaining general implementation aspects for attaching the IBM Spectrum Accelerate™ family to VMware ESXi deployments, the paper focuses on components that are enabled by IBM Spectrum Connect v3.4. This paper is intended for planning to use or implementing the IBM Spectrum Accelerate family of storage systems in a VMware environment.